Ethics of Health Information Sharing and Social Relationships at End of Life in Assisted Living. (April 2022) - Cooke, Emma; Perkins, Molly M.; Doyle, Patrick; Kinlaw, Kathy; Wack, Kevin; Vandenberg, Ann E.
Given an observed tension between perceived privacy restrictions and meaningful social connection in assisted living (AL) and using a relational perspective, we conducted a secondary thematic analysis of health information sharing practices among residents and their care partners in one large urban AL community in metropolitan Atlanta. Data included in-depth interviews with residents ( n = 26), family members ( n = 20), AL staff ( n = 11), and external care workers ( n = 4) as well as ethnographic data from observations and informal conversations conducted with these participants and others. Findings showed that health information sharing among residents was helpful in building social relationships; barriers to this communication contributed to isolation. Inappropriate public exchange of residents' healthcare information hindered building these relationships. Negotiating privacy boundaries for health information sharing was an ongoing confusing process across the community. Based on the findings, we propose new guidelines for health information sharing and additional privacy training for residents and care partners.